Socioproductive changes in the fruit and vegetable industry: reconfiguration of work and production - Canafoglia , Eliana Celeste (Instituto de Investigaciones Socioeconómicas, 2019)
Based on recent research about the dinamic of the non-wine fruit and vegetable industry in the province of Mendoza, we reflect on the situation of work and local production. Changes in macroeconomic policy (monetary circulation, exchange and interest rates), trade liberalization (deregulation of imports of products similar to the ones produce in the regional economy) and the situation of the main trading partner countries, particularly buyers of products from agricultural origin in Mendoza (Brazil and the United States) are conditioning exchange and the continuity in the local production. The prevalence of the logic of large distribution chains subjugate the conditions of such exchange, obstructing other distribution and marketing channels (which means, difficults the process of valorization). This logic is causing serious troubles in the reproduction of agroindustrial producers and smes from Mendoza. We aim to evidence that the strategies followed by them, deteriorate sources of employment and substantials areas of territorial production. The methodology follow is based on secondary data, documentary analysis and the collection of testimonies of workers, producers and businessmen.